Satuan Pendidikan Dalam Konteks Akreditasi Pendidikan - Malarita (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The great benefits felt by each customer or user of an education unit service, is a manifestation of the quality of the education unit in implementing educational and learning processes. Prioritizing the needs of customers or service users is the reference for the education unit to make changes for the better every time. Educational unit service users are interest groups who really hope that each education unit is able to do the best for the interests of society as users of education services. For this reason, accreditation is important to do so that each education unit meets all the requirements that enable it to have objective, accountable authority and a sense of accountability to its interest groups or stakeholders. This accreditation is carried out to ensure that the community as stakeholders are not ignored by all their interests and needs.